2013
DOI: 10.1186/1475-2875-12-378
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a HRP-2/pLDH based rapid diagnostic test at the Bangladesh-India-Myanmar border areas for diagnosis of clinical malaria

Abstract: BackgroundThe rapid diagnostic test (RDT) has been adopted in contemporary malaria control and management programmes around the world as it represents a fast and apt alternative for malaria diagnosis in a resource-limited setting. This study assessed the performance of a HRP-2/pLDH based RDT (Parascreen® Pan/Pf) in a laboratory setting utilizing clinical samples obtained from the field.MethodsWhole blood samples were obtained from febrile patients referred for malaria diagnosis by clinicians from two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In the present study, detection was based on HRP-II antigen of P. falciparum and pLDH of P. vivax in whole blood and the sensitivity and specificity of RDT was found to be 96.6% and 85% for P. vivax. In various studies from India, sensitivity and specificity of RDTs have been reported from 84.2% to 98.70% and 96.5% to 98.9% [41][42][43] which corroborates with present study. In a country such as India where P. vivax is responsible for causing uncomplicated and severe infection, the limited sensitivity of current used RDTs in detection of P. vivax is considered to be the major obstacle to long-term disease control programs and should be considered an urgent development goal in this field.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, detection was based on HRP-II antigen of P. falciparum and pLDH of P. vivax in whole blood and the sensitivity and specificity of RDT was found to be 96.6% and 85% for P. vivax. In various studies from India, sensitivity and specificity of RDTs have been reported from 84.2% to 98.70% and 96.5% to 98.9% [41][42][43] which corroborates with present study. In a country such as India where P. vivax is responsible for causing uncomplicated and severe infection, the limited sensitivity of current used RDTs in detection of P. vivax is considered to be the major obstacle to long-term disease control programs and should be considered an urgent development goal in this field.…”
Section: Discussionsupporting
confidence: 92%
“…Elahi 2013 estimated a sensitivity of 91% and specificity of 99% for both PCR and microscopy; Bendezu 2010 estimated a sensitivity of 76% and specificity of 98% with PCR, and sensitivity of 77% and specificity of 99% with microscopy. The accuracy of CareStart Pf/Pan reported by Xiaodong 2013 was similar for both reference standards with sensitivity of 91% and specificity of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…The few studies to evaluate RDT for P. vivax infection in non-pregnant individuals report varying performance [ 19 , 20 , 44 ]. The prevalence of P. vivax infections was lower than expected, and it was a rare cause of clinical malaria in the present study.…”
Section: Discussionmentioning
confidence: 99%